Synthesis and characterization of zinc oxide polycaprolactone nanocomposites using rectangular waveguide and microstrip techniques - Yakubu, Abubakar (2015)
A growing number of demanding applications in high frequency electronics and telecommunications depends on the absorbing properties of materials. The electromagnetic properties of microwave absorbers and radar-absorbing materials are critical issues that need to be resolved in many military applications dealing with reduction of radar signature of aircraft and ships. For industrial equipment and home appliance applications, the Electromagnetic Compatibility Compliance Directive (ECCD), demands electromagnetic interference side effects be eliminated or marginally minimised. The equipment must not disturb radio and telecommunication as well as other appliances. Additionally, the ECCD also governs the immunity of such equipment to interference and seeks to ensure that this equipment is not disturbed by radio emissions when used as intended. Many type of absorbing materials are commercially available. However, many are expensive and not environmentally friendly. This thesis describes the synthesis and characterization of zinc oxide (ZnO) nanoparticles and ZnO-PCL nanocomposites using the microwave irradiation and melt blend techniques respectively. Two types of pellets with dimension of 6.0 cm X 3.6 cm and 0.11 cm X 0.22 cm were prepared for the measurement of complex permittivity of the different % of the composites using open ended coaxial probe (OEC), while the latter dimension were used in a rectangular waveguide (RWG) in measuring both the permittivity and permeability of the different % composites. Comparison of permittivity between OEC and RWG results were carried out for all materials used in this study (PTFE, PCL and composites with different percentages of ZnO nanofillers). The effect of the different % ZnO nanofiller on the permittivity of the composites were also investigated. Attenuation, power loss and absorption due to sample thickness and ZnO nanofiller inclusion in the composites were investigated using finite element method (FEM) and RWG methods, whilst transmission and reflection coefficient were measured, simulated and calculated using RWG, FEM, and Nicholson Ross Weir (NRW) methods respectively. Microstrip and FEM techniques were used to determine both the transmission and reflection coefficients and electric field distribution for the different % ZnO- PCL nanocomposites pellets when placed on top a microstrip. Comparison of the measured and calculated scattering parameters were also investigated. Furthermore, the results obtained from the scattering parameters were used to determine the attenuation of the different % of ZnO-PCL nanocomposites pellets. Finally, the effect of the different % ZnO nanofiller on electric field was investigated by visualizing the electric field distribution of the ZnO-PCL nanocomposites pellets placed on top a microstrip using finite element method. Findings from investigations showed that the complex permittivity values obtained using the OEC method were in good agreement with the RWG technique, whilst increase of ZnO nanofiller percentage into the polymer matrix increased the dielectric constant, loss factor, attenuation, absorption, real permeability, imaginary permeability and reflection coefficient of the composites. The attenuation obtained for the 70 % filler composition was -18 dB which is good for microwave absorption whilst the microwave irradiation technique was able to synthesize ZnO nanoparticles with an average particle size of 57.5 nm.